2020
DOI: 10.1097/jac.0000000000000310
|View full text |Cite
|
Sign up to set email alerts
|

A Closer Examination of the Patient Experience in the Ambulatory Space

Abstract: This qualitative study explores key patient experience impressions responsible for driving quality. Differences between primary and specialty care patient perspectives were analyzed using a mixed-methods design in high-, median-, and low-quality performing practices. We found that primary care patients highly value provider listening, time spent with provider, and consistent and effective coordination of care. Specialty care patients were found to highly value provider clinical skill acumen/outcomes, being kep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The researchers concluded that differing patient types attach greater value to different elements of their health care experiences. (Jurdi et al, 2020, p. 89)…”
Section: Current Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…The researchers concluded that differing patient types attach greater value to different elements of their health care experiences. (Jurdi et al, 2020, p. 89)…”
Section: Current Literaturementioning
confidence: 99%
“…With the explosion of consumerism in one of the most rapidly changing and regulated industries, understanding today's US health care consumer highlights the importance of prioritizing the delivery of patient- and family-centered care. Berwick (2009) and the Institute of Medicine (IOM, 2001) assert that patient-centeredness is a pillar of quality; therefore, improving the overall patient experience is fundamental for improving health care quality (Jurdi et al, 2020).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Patient experience is measured by patient feedback from the Consumer Assessment of Healthcare Providers and System Clinician and Group Surveys (4). The Press Ganey survey is one of the most commonly used surveys to assess patient feedback on the outpatient experience (5).…”
Section: Introductionmentioning
confidence: 99%